Impact of Water-Cement Ratio and Desert Sand Powder on the Mechanical Properties of Eco-Self-Compacting Concrete - Said Zaouai; Farid Benmerioul; Abdelkadir Makkani; Ahmed Tafraoui; Rachid Rabehi (The Journal of Engineering and Exact Sciences)
This study investigates the effects of varying water-cement (w/c) ratios (0.40-0.55) and the incorporation of 10% powdered dune sand from Taghit, Algeria, on eco-self-compacting concrete (E-SCC) properties. The research explores the potential of utilizing abundant desert sand resources as a partial cement replacement while maintaining concrete performance. Through experimental analysis and response surface methodology (RSM), the study demonstrates that lower w/c ratios significantly enhance compressive strength, with optimal performance achieved at a 0.40 w/c ratio reaching 55 MPa. The findings reveal that decreasing the w/c ratio reduces porosity and improves the concrete's overall structural integrity. Capillary absorption tests indicate that while E-SCC with a 0.40 w/c ratio shows slightly higher initial absorption rates over the first two hours, it demonstrates better long-term performance over 24 hours compared to higher w/c ratios. The results confirm that incorporating 10% powdered dune sand while maintaining a low w/c ratio can produce high-performance eco-self-compacting concrete that meets industry standards for workability and strength, offering a sustainable alternative for construction applications.